Darwin’s theory of biological evolution seen from the point of view of modern physics - Krupska, Aldona (Hybris, 2013)
This paper aims to show the influence of 20th century quantum mechanics and the theory of relativity on the philosophical problems of Darwin’s theory of biological evolution. Evolution as a non-relativistic being can be attributed only to the process as a whole. Quantum mechanics and the theory of relativity are not compatible with the evolution process of separate elements of the system. It seems to be in contradiction to Darwin’s theory of evolution as a slow and gradual process of separate elements in the biological system. According to many scientists and philosophers of science the Darwin’s theory does not explain the whole Universe evolution as well as does not explain the origin of life. Explanation of events and processes, reliance on concepts not laws, refutation of typology by Darwin theory of evolution are not established by standards of scientific reasoning. Many scientific facts from modern physics indicate that Darwin’s theory of evolution is in crisis.